ANTIULCER ACTIVITY OF AGNIMUKHA CHURNA (International Journal of Ayurveda and Pharma Research, 2015)
Background: Agnimukha Churna is a popular Ayurvedic formulation, composed of herbs and spices, used for treatment of gastrointestinal disorders by traditional healers.Objectives: In present study, we have to subject the pharmacognostic, phytochemical test and to evaluate the anti-ulcer activity of Agnimukha Churna.Material and Methods: Study was carried out, by using two methods i.e., ethanol induced ulcers (5ml/kg, Absolute ethanol) and aspirin induced ulcers (200mg/kg) in rats pretreated with the doses of, Alcoholic Extract of Churna (AEC) (200mg/kg), Hydro-alcoholic Extract of Churna (HAEC) (200mg/kg), Ranitidine (20mg/kg). After 1 hour in ethanol induced method and 4 hour in aspirin induced method rat was sacrificed and stomach was removed for observation of ulcer scores, ulcer index and percentage of inhibition.Results: The AEC and HAEC maintain the integrity of gastric mucosa by virtue of its effect on offensive and defensive gastric mucosal factors. AEC and HAEC significantly (P